An Expanded 2D Fused Aromatic Network with 90‐Ring Hexagons. (2nd December 2021) - Riaño, Alberto; Strutyński, Karol; Liu, Meng; Stoppiello, Craig T.; Lerma‐Berlanga, Belén; Saeki, Akinori; Martí‐Gastaldo, Carlos; Khlobystov, Andrei N.; Valenti, Giovanni; Paolucci, Francesco; Melle‐Franco, Manuel; Mateo‐Alonso, Aurelio
Abstract: Two‐dimensional fused aromatic networks (2D FANs) have emerged as a highly versatile alternative to holey graphene. The synthesis of 2D FANs with increasingly larger lattice dimensions will enable new application perspectives. However, the synthesis of larger analogues is mostly limited by lack of appropriate monomers and methods. Herein, we describe the synthesis, characterisation and properties of an expanded 2D FAN with 90‐ring hexagons, which exceed the largest 2D FAN lattices reported to date. Abstract : A two‐dimensional fused aromatic network with a honeycomb lattice constituted of 90‐ring hexagons, the largest yet reported, was obtained by solvothermal synthesis.